Murder in Samarkand a British Ambassador's controversial defiance of tyranny in the War on Terror - Murray, Craig 1958- (Mainstream Pub., 2007)
When Craig Murray arrived in Uzbekistan to take up his post in 2002, he was a young ambassador with a brilliant career and a taste for whisky and women. Here, Murray looks at the dark and dirty underside of the War on Terror.